2005
DOI: 10.4049/jimmunol.175.9.5975
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic AMP Response Element Modulator Regulates Transcription of the TCR ζ-Chain

Abstract: Systemic lupus erythematosus T cells display decreased amounts of TCR ζ mRNA that results in part from limited binding of the transcriptional enhancer Elf-1 to the TCR ζ promoter. We have identified a new cis-binding site for the cAMP response element (CRE) modulator (CREM) on the TCR ζ promoter, centered on the −390 nucleotide. Transfection of T cells with an antisense CREM α plasmid reduced the binding of CREM to the TCR ζ promoter, as shown by chromatin and reporter chromatin immunoprecipitation assays, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…Previous studies have shown that forced overexpression of FcR␥ leads to the down-regulation of the TCR -chain (9), whereas reconstitution of the TCR -chain expression in SLE T cells results in the decrease of the previously up-regulated FcR␥ (10). In contrast to the TCR gene that is known to be regulated by the transcription factors Elf-1 and CREM (cAMP response element modulator) (11,12), the transcription factor or factors that are involved in the transcription of the FcR␥ gene have not been defined.…”
Section: T He Fc Receptor (Fcr)mentioning
confidence: 99%
“…Previous studies have shown that forced overexpression of FcR␥ leads to the down-regulation of the TCR -chain (9), whereas reconstitution of the TCR -chain expression in SLE T cells results in the decrease of the previously up-regulated FcR␥ (10). In contrast to the TCR gene that is known to be regulated by the transcription factors Elf-1 and CREM (cAMP response element modulator) (11,12), the transcription factor or factors that are involved in the transcription of the FcR␥ gene have not been defined.…”
Section: T He Fc Receptor (Fcr)mentioning
confidence: 99%
“…37 Two negative regulators of Ras/ERK signaling associated with anergy (namely, DGK 38,39 and Ras p21 protein activator 1 40 ) were transcriptionally induced within OT-I cells undergoing deletion. In addition, other negative regulators of either TCR signaling (cAMP-responsive element modulator 41 and thymocyte selection-associated HMG box gene [Tox] 42 ) or cell-surface receptor signaling (LIG1 43 and PTP 44 ) were also up-regulated during deletion. Furthermore, several genes whose up-regulation (cAMP-responsive element modulator, 45 PTP, 46 IKAROS family zinc finger 2 [Helios], 47 Pleckstrin homology, Sec7 and coiled-coil domains3 [GRP1], 48 and Nr4a3 [Nor1] 35 ) or down-regulation (GzmB 49 ) is associated with the anergic state, were found to also be up-or down-regulated, respectively, during deletion.…”
Section: Molecular Parallels Between Deletion and Anergymentioning
confidence: 99%
“…It has been reported that SLE T cells display elevated levels of CREM␣ due to increased CREM promoter activity that even reflects SLE disease activity (18,21). Additional immune cell-relevant target genes have been identified that are transregulated by CREM␣ such as transcription factor c-fos, TCR/ CD3 and antigen-presenting cell molecule CD86 (22)(23)(24). Apart from its direct transcriptional effects, CREM␣ is also involved in epigenetic mechanisms of gene regulation because it may recruit histone deacetylase (HDAC)1 or DNA methyltransferase (DNMT)3a to specific regulatory gene sequences; however, it fails to mobilize histone acetyltransferase activity of p300 (25)(26)(27).…”
Section: Il-17a Is a Proinflammatory Cytokine That Is Produced By Spementioning
confidence: 99%